1992
DOI: 10.1002/jez.1402630405
|View full text |Cite
|
Sign up to set email alerts
|

Osmotic and ionic regulation during hypoxia in the medicinal leech, Hirudo medicinalis L.

Abstract: The concentrations of inorganic and organic ions and osmolality in the blood of the medicinal leech, Hirudo medicinalis, were determined during normoxia and hypercapnic and hypocapnic hypoxia. In normoxic animals, the blood sodium concentration was 124.5 +/- 4.2 mmol/l and the total cation concentration was 132.2 +/- 4.3 mEq/l (mean +/- S.D.). Major anionic compounds were chloride (40.8 +/- 1.6 mmol/l), bicarbonate (8.4 +/- 1.3 mmol/l), and organic anions (42.5 +/- 2.3 mEq/l). Among the latter, malate accounts… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

1993
1993
2006
2006

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 19 publications
1
3
0
Order By: Relevance
“…[Mg 2+ ] T in leech blood as determined by atomic absorption spectrometry has a mean ± SD of 1.64 ± 0.52 mmol/l (n = 3, unpublished results). At an extracellular malate concentration of 30 mmol/l and a K app of 15.5 mmol/l, as determined in the present study, this corresponds to a [Mg 2+ ] o of 0.57 ± 0.18 mmol/l, which is in excellent agreement with the [Mg 2+ ] o of 0.6 ± 0.2 mmol/l determined by Hildebrandt & Zerbst-Boroffka (12). [Mg 2+ ] o in the leech is thus strongly buffered.…”
Section: Biological Relevance Of the Bindingsupporting
confidence: 91%
See 1 more Smart Citation
“…[Mg 2+ ] T in leech blood as determined by atomic absorption spectrometry has a mean ± SD of 1.64 ± 0.52 mmol/l (n = 3, unpublished results). At an extracellular malate concentration of 30 mmol/l and a K app of 15.5 mmol/l, as determined in the present study, this corresponds to a [Mg 2+ ] o of 0.57 ± 0.18 mmol/l, which is in excellent agreement with the [Mg 2+ ] o of 0.6 ± 0.2 mmol/l determined by Hildebrandt & Zerbst-Boroffka (12). [Mg 2+ ] o in the leech is thus strongly buffered.…”
Section: Biological Relevance Of the Bindingsupporting
confidence: 91%
“…From equation [4], the ratio of the concentrations is: [12] [X-Anion (n -2)-]: Substituting for [Anion n-] from equation [12] in equation [10] gives [25] Substitution of equations [20] and [21] in equation [25] [27] Substitution of equations [20] and [21] in equation [27] [ [30] [X 2+ ]: Substituting equations [20] and [21] in equation [22]:…”
Section: Discussionmentioning
confidence: 99%
“…This species might be more tolerant to low oxygen partial pressure. Hildebrandt & Zerbst (1992) found that sodium concentrations in the blood of medicinal leeches decreased significantly after 96 h in hypoxia. However, sodium levels in a brackish water isopod were found not to be affected by hypoxia and Na + concentrations decreased only in anoxia (Hagerman & Szaniawska, 1991).…”
Section: Discussionmentioning
confidence: 97%
“…Cl − is the major strong anion in all physiological saline environments for vertebrates, with bicarbonate as the major (anionic) buffer, but is partially replaced by organic anions in many invertebrates (Prosser and Brown, 1961), such as malate in the medicinal leech (Hildebrandt and Zerbst‐Boroffka, 1992). All living cells express a combination of transporters and ion channels to move Cl − , bicarbonate, and other anions across cell membranes.…”
Section: Introductionmentioning
confidence: 99%